Mexico : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press Release; Staff Supplement; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
The government has successfully maintained external, financial, and fiscal stability despite the deepest recession in decades. However, Mexico is bearing a very heavy humanitarian, social, and economic cost from COVID-19, including over half a million excess deaths, sizable under-employment, and an increase in poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy